2022
DOI: 10.3390/healthcare10030436
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Self-Management among Non-Dialysis Chronic Kidney Disease Patients

Abstract: Aim: The new trend in the management of chronic kidney disease (CKD) is based on the adoption of self-management approaches. However, there is a paucity of research assessing the level of self-management behavior among non-dialysis patients. The aim of the study is to assess the association between self-management behaviors and the level of disease-specific knowledge among non-dialysis CKD patients. In addition, this study aimed to assess the predictors of self-management among non-CKD patients. Methods: A con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Across the studies [ 20 26 ], patients highlighted their need for CKD-related education. Almutary and Tayyib [ 27 ] observed that knowledge was independently associated with self-management in a sample of patients who have CKD without KRT. These findings potentially reflect the empowering effects of CKD-related education.…”
Section: Discussionmentioning
confidence: 99%
“…Across the studies [ 20 26 ], patients highlighted their need for CKD-related education. Almutary and Tayyib [ 27 ] observed that knowledge was independently associated with self-management in a sample of patients who have CKD without KRT. These findings potentially reflect the empowering effects of CKD-related education.…”
Section: Discussionmentioning
confidence: 99%
“…One predictor of inadequate engagement in CKD self-care behavior is older age, a trend attributed to older adults’ lower capacity for engagement relative to younger adults ( 5 ). Compared to younger counterparts, older adults face unique challenges in meeting personal care and support needs, such as multi-morbidity, functional limitations in activities of daily living, cognitive decline, frailty, socioeconomic disadvantage, social isolation, and geriatric conditions ( 6 ).…”
Section: Introductionmentioning
confidence: 99%